ANALISIS KOMPONEN KIMIA DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK RIMPANG JAHE MERAH (Zingiber officinale Rosc. Var rubrum) - Rachmin Munadi (Cokroaminoto Journal of Chemical Science, 2020)
Study on chemical component analysis and antioxidant activity test of red ginger rhizome extract (Zingiber officinale Rosc. Var rubrum) has been conducted. The red ginger rhizome was extracted by maceration method and using methanol as a solvent. The antioxidant activity was tested by using DPPH method with wavelength 515 nm. The result showed that positively, red ginger rhizome extract containing flavonoid, tannins, saponins, alkaloids and terpenoids compounds, whereas, the antioxidant antioxidant anticity test got value IC50 10, 35µg/mL classified as very strong.